110 Systematic Analysis of European Society of Cardiology Guidelines: What Do We Actually Base Our Practice On?. (31st May 2014) - Sau, Arunashis; Cole, Graham; Cook, Christopher; Shun-Shin, Matthew; Francis, Darrel
Abstract : Background: The European Society of Cardiology's guidelines "present all the relevant evidence on a particular clinical issue" to clinicians, being designed to be "helpful in everyday clinical medical decision-making".Statements are accompanied by one of three Levels of Evidence: A (multiple randomised controlled trials (RCTs) or meta-analyses), B (large non-randomised studies or one RCT) or C (expert opinion, small/retrospective studies or registry data). We evaluated the Levels of evidence underlying the guideline documents as a whole to establish whether, as time progresses, they are providing clinicians with recommendations of increasing scientific soundness. Methods: We systematically analysed all current and past guideline documents from the European Society of Cardiology, which offered recommendations with Levels of Evidence or Class of Recommendation.We recorded the Level of Evidence available for each recommendation. Two independent observers extracted the Level of Evidence provided for each recommendation.A third observer settled any disagreements. Results: There are now over 3000 active guideline recommendations to steer the practice of cardiologists. Almost half (49.6%) of recommendations are Level C and are based on no more than opinion or bias-vulnerable observational reports.Under a fifth (18.3%) have the highest recommendation level, A and are based on randomised controlled trials or meta-analyses.Level B accounts for the remaining 32.1%. There has been a large increase in the number of guideline recommendations over time (Figure 1 ). Revision of an individual guideline document increases the total number of recommendations (median of +7.5, IQR 0 to +49).Recommendations based on the lowest Level of Evidence (C) were more frequently added (median of +17.5, IQR 0 to +36) than Level B (+5.5, IQR -0.5 to +14.75), which were in turn more commonly added than recommendations with the highest Level of Evidence (A) (+3.5, IQR 0 to +11). Areas of cardiology differed substantially in Levels of Evidence. ACE inhibitors had the highest proportion of high-level evidence (86% Level A, 7% B and 7% C) whilst Aortic Dissection the lowest (100% Level C). Over 2/3 of guideline documents had less than 1/3 of their recommendations based on Level A.Only 2 had over 50% of recommendations based on Level A. Conclusions: Cardiologists are faced with over 3000 evidence-based instructions to steer their clinical practice.Almost half have no RCT data whatsoever.Recommendations continue to be added, but these are most commonly based on opinion, not RCT proof. We recommend that if guidelines are to direct clinical action they should restrain themselves to making a smaller number of clear recommendations that are based on reliable (i.e. RCT) evidence.